The role of temperature on dielectric relaxation and conductivity mechanism of dark conglomerate liquid crystal phase - Yıldız, Alptekin; Okutan, Mustafa; Canli, Nimet; Ozdemir, Zeynep; Ocak, Hale; Eran, Belkiz Bilgin (Elsevier BV, 2016)
Abstract In this study, dielectric properties and ac conductivity mechanism of the bent-core liquid crystal 3′-{4-[4-(3,7-Dimethyloctyloxy)benzoyloxy]benzoyloxy}-4-{4-[4-[6-(1,1,3,3,5,5,5-heptamethyltrisiloxan-1yl)hex-1-yloxy]benzoyloxy]benzoyloxy}biphenyl ( DBB ) have been analyzed by impedance spectroscopy measurements at different temperatures. According to the polarizing microscopy results, DBB liquid crystal compound exhibits a dark conglomerate mesophase (DC [*] phase) which can be identified by the occurrence of a conglomerate of domains with opposite chirality. The chiral domains of this low-birefringent mesophase become more visible by rotating the polarizer. The variation of the real ( e ′) and imaginary ( e ″) parts of dielectric constant with angular frequency and Cole–Cole curves of DBB have been analyzed. The fitting results for dispersion curves at different temperatures revealed that DBB system exhibits nearly Debye-type relaxation except for 125 °C. Moreover, it has been determined that while the relaxation frequencies shift to higher frequencies as the temperature increases from 25 °C to 125 °C, the peak intensities remarkably decrease with increasing temperature. According to Cole–Cole plot and phase angle versus frequency curve, it has been determined that DBB LC may have a possibility of utilizing as a super-capacitor at room temperature. Furthermore, it has been found that the conductivity mechanism of the DBB alters from Correlated Barrier Hoping (CBH) model to Quantum Tunneling Model (QMT) with in increasing temperature at high frequency region. In terms of CBH model, optical band gaps at 25 °C and 75 °C temperatures have also been calculated. Finally, activation energies for some selected angular frequencies have also been calculated.